Future Skills for IT Industry: A study of IT professionals in Europe for managing talent in IT industry - Sabharwal, Sharanjit Singh (2020)
In current times of rapid technological developments, disruptions, fierce competition and changing customer needs, success of Information Technology organisations depends on their agility and adaptability to external environments. Talent is a key resource for building organisational agility and to enable innovation. But the opportunities and challenges that Industry 4.0 brings, need organisations to adopt appropriate talent management practices in view of the future. In light of this, the paper attempts to identify talent required in IT industry in Europe through an exploratory study carried out with IT professionals working across Europe. The paper reviews academic and practitioners’ literature to understand the talent needs for future and assesses the gap that currently exists through implementation of a survey. Through a reflection of its findings it provides some recommendations for practice.